Alterations in cardiac DNA methylation in human dilated cardiomyopathy. Issue 3 (22nd January 2013) - Haas, Jan; Frese, Karen S.; Park, Yoon Jung; Keller, Andreas; Vogel, Britta; Lindroth, Anders M.; Weichenhan, Dieter; Franke, Jennifer; Fischer, Simon; Bauer, Andrea; Marquart, Sabine; Sedaghat‐Hamedani, Farbod; et al.
Abstract Dilated cardiomyopathies (DCM) show remarkable variability in their age of onset, phenotypic presentation, and clinical course. Hence, disease mechanisms must exist that modify the occurrence and progression of DCM, either by genetic or epigenetic factors that may interact with environmental stimuli. In the present study, we examined genome‐wide cardiac DNA methylation in patients with idiopathic DCM and controls. We detected methylation differences in pathways related to heart disease, but also in genes with yet unknown function in DCM or heart failure, namely Lymphocyte antigen 75 (LY75), Tyrosine kinase‐type cell surface receptor HER3 (ERBB3), Homeobox B13 (HOXB13) and Adenosine receptor A2A (ADORA2A). Mass‐spectrometric analysis and bisulphite‐sequencing enabled confirmation of the observed DNA methylation changes in independent cohorts. Aberrant DNA methylation in DCM patients was associated with significant changes in LY75 and ADORA2A mRNA expression, but not in ERBB3 and HOXB13. In vivo studies of orthologous ly75 and adora2a in zebrafish demonstrate a functional role of these genes in adaptive or maladaptive pathways in heart failure.